STUDENT ENGAGEMENT IN PROMOTING ENGLISH AS AN INTERNATIONAL LANGUAGE: A PARENTAL AWARENESS CAMPAIGN IN THAI SCHOOLS - Mediena, Yasmin Elfa; Putra, Aidil Syah; Rohim, Abdul (Universitas Muhammadiyah Mataram, 2025)
Abstrak: Program pengabdian masyarakat ini dilaksanakan dengan tujuan meningkatkan kesadaran orang tua dalam mendukung pembelajaran bahasa Inggris sebagai bahasa internasional melalui keterlibatan aktif siswa dalam kegiatan kampanye edukatif. Kegiatan ini merupakan bagian dari program pertukaran pelajar yang dilakukan oleh mahasiswa Indonesia di Lukmanulhakeem School, Yaha, Provinsi Yala, Thailand Selatan. Pelaksanaan program berlangsung selama dua bulan, terhitung sejak 12 November 2024 hingga 7 Januari 2025, melalui empat tahapan strategis, yaitu: koordinasi awal dengan tenaga pendidik, penggalangan dukungan dari orang tua, pelaksanaan pembelajaran intensif di lingkungan sekolah, dan penguatan keterlibatan keluarga dalam proses pembelajaran. Hasil pelaksanaan program menunjukkan bahwa kolaborasi antara pihak sekolah, keluarga, dan siswa memberikan kontribusi signifikan terhadap peningkatan kompetensi berbahasa Inggris siswa. Meskipun sebagian orang tua memiliki keterbatasan dalam penguasaan bahasa Inggris, partisipasi mereka dalam kegiatan kampanye seperti Family English Challenge dan English for Life Simulation memberikan dampak positif terhadap motivasi dan kepercayaan diri siswa dalam berkomunikasi. Dengan demikian, pendekatan pembelajaran berbasis sosial-edukatif terbukti efektif dalam membentuk kompetensi abad ke-21, khususnya keterampilan komunikasi lintas budaya di wilayah yang memiliki keterbatasan akses terhadap pendidikan bahasa asing.Abstract: This community service initiative was carried out with the aim of raising parental awareness in supporting English language learning as an international language through the active involvement of students in educational campaign activities. The programme formed part of a student exchange initiative undertaken by Indonesian university students at Lukmanulhakeem School, Yaha, Yala Province, Southern Thailand. The service project was conducted over a two-month period, from 12 November 2024 to 7 January 2025, and was implemented through four strategic stages: initial coordination with teaching staff, mobilising parental support, conducting intensive language learning activities within the school environment, and reinforcing family engagement in the learning process. The outcomes of the programme revealed that collaboration among schools, families, and students played a significant role in enhancing pupils’ English language proficiency. Although some parents had limited proficiency in English, their participation in campaign activities such as the Family English Challenge and English for Life Simulation positively contributed to students' motivation and confidence in communication. Thus, a socially and educationally driven approach to language learning proved effective in fostering 21st-century competencies, particularly cross-cultural communication skills, in areas with limited access to foreign language education.